Domestic Violence by a Husband Against His Wife (Case Study of Decision Number 270/Pid.Sus/2022/PN Bnj) - Karolus Kanefo Lafau; July Esther; Hisar Siregar (Dinasti Research, 2024)
Currently, women are the main victims of domestic violence throughout Indonesia. Domestic violence generally refers to acts such as verbal abuse, physical violence, coercion, and threats. Domestic violence has always been a concern in various sectors. Although considered very dangerous by the government, this crime continues to be committed in the general public. Domestic violence, especially the brutality of men against their wives, not only causes real torture, but also mental suffering. Therefore, victims of domestic violence must receive maximum legal protection. Basically, marriage is something sacred in society. Because of the bond of marriage between a man and a woman, the marriage is legally binding in the form of the rights and responsibilities of the husband towards his wife, and the obligations of the wife towards her husband. According to Law Number 1 of 1974 Article 1 concerning Marriage, marriage is a physical and spiritual union between a man and a woman as husband and wife with the aim of realizing a happy and eternal family based on faith in God Almighty. Domestic violence is any act that causes misfortune or physical, sexual, or mental suffering to a person, especially women. The regulation of domestic violence is regulated in Law Number 23 concerning the Elimination of Domestic Violence.